A prospective, multicentre phase II trial of low-dose erlotinib in non-small cell lung cancer patients with EGFR mutations pretreated with chemotherapy: Thoracic Oncology Research Group 0911. Issue 14 (September 2015) - Yamada, Kazuhiko; Aono, Hiromi; Hosomi, Yukio; Okamoto, Hiroaki; Kato, Terufumi; Komase, Yuko; Nishikawa, Masanori; Azuma, Koichi; Takeoka, Hiroaki; Okuma, Yusuke; Nakahara, Yoshiro; Sato, Akira; et al.
Abstract Background Low-dose erlotinib may be as effective as gefitinib or erlotinib at full dose in non-small cell lung cancer (NSCLC) patients with activating mutations of the epidermal growth factor receptor (EGFR) gene. Methods Patients with chemotherapy pretreated NSCLC harbouring EGFR mutations received erlotinib at 50 mg/d until disease progression or unacceptable toxicities. The dose was escalated to 150 mg/d in patients showing no response (i.e. without major tumour shrinkage according to Response Evaluation Criteria in Solid Tumours (RECIST)) to the initial dose during the first 4 weeks. The primary end-point was the objective response rate at the dose of 50 mg/d. Results Thirty-four patients from seven institutes were enrolled. The study was closed early when no response was confirmed in 15 patients, excluding the possibility that the primary end-point would be met. The objective response and disease control rates at the dose of 50 mg/d as determined by an independent review committee were 54.5% and 84.8%, respectively. Four additional patients achieved partial response with increased 150 mg/d dose. Progression-free survival and median survival times during the entire period of the study were 9.5 and 28.5 months, respectively. Treatment-related toxicities were generally mild, the most common being skin disorders and diarrhoea. Only one case experienced grade 3 toxicity, which was transient increase of hepatic enzymes. Conclusion The primary end-point was not met; low-dose erlotinib is not recommended for fit patients with NSCLC harbouring EGFR mutations. However, it may merit further evaluation for elderly or frail patients.